2015
DOI: 10.1186/s12896-015-0116-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Fructooligosaccharides by IslA4, a truncated inulosucrase from Leuconostoc citreum

Abstract: BackgroundIslA4 is a truncated single domain protein derived from the inulosucrase IslA, which is a multidomain fructosyltransferase produced by Leuconostoc citreum. IslA4 can synthesize high molecular weight inulin from sucrose, with a residual sucrose hydrolytic activity. IslA4 has been reported to retain the product specificity of the multidomain enzyme.ResultsScreening experiments to evaluate the influence of the reactions conditions, especially the sucrose and enzyme concentrations, on IslA4 product speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…Microbial levans are produced by a wide range of different gram‐negative and gram‐positive bacteria (see Table below). On the other hand, microbial inulins (a backbone of β‐2,1 linkages between fructofuranosyl units with β‐2,6 branches) are only produced by a limited number of gram‐positive bacteria belonging to genera of Lactobacillus , Leuconostoc , Streptococcus , and Weissella (Anwar, Kralj, van der Maarel, & Dijkhuizen, ; Malang, Maina, Schwab, Tenkanen, & Lacroix, ; Peña‐Cardeña, Rodríguez‐Alegría, Olvera, & Munguía, ; Rosell & Birkhed, ), and the literature is very scarce as compared to levan. In fact, levan production by different microbes has been studied well for over a few decades, and it was revealed that levan shows significantly different physicochemical properties such as branching degree, molecular weight, intrinsic viscosity, and functional properties such as adhesive strength and immunogenic activity, depending on the microbial strains used and various fermentation conditions.…”
Section: Fructans and The Gh‐j Clan Enzymesmentioning
confidence: 99%
“…Microbial levans are produced by a wide range of different gram‐negative and gram‐positive bacteria (see Table below). On the other hand, microbial inulins (a backbone of β‐2,1 linkages between fructofuranosyl units with β‐2,6 branches) are only produced by a limited number of gram‐positive bacteria belonging to genera of Lactobacillus , Leuconostoc , Streptococcus , and Weissella (Anwar, Kralj, van der Maarel, & Dijkhuizen, ; Malang, Maina, Schwab, Tenkanen, & Lacroix, ; Peña‐Cardeña, Rodríguez‐Alegría, Olvera, & Munguía, ; Rosell & Birkhed, ), and the literature is very scarce as compared to levan. In fact, levan production by different microbes has been studied well for over a few decades, and it was revealed that levan shows significantly different physicochemical properties such as branching degree, molecular weight, intrinsic viscosity, and functional properties such as adhesive strength and immunogenic activity, depending on the microbial strains used and various fermentation conditions.…”
Section: Fructans and The Gh‐j Clan Enzymesmentioning
confidence: 99%
“…The presence of three products (6-kestose, 1-kestose and neo-kestose) reflects the low regioselectivity of levansucrase in the first fructosyl transfer to a sucrose molecule. The synthesis of these three kestoses has been reported in reactions catalyzed by both levansucrases and inulosucrases 24 , 27 , 31 , suggesting that this lack of regioselectivity when sucrose is the acceptor molecule may be a common characteristic among fructansucrases. The relaxed regiospecificity is consistent with the result of structure-function analysis that locate bond type specificity of fructansucrases in residues further away from the +2 substrate subsite 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to levan, both the whole culture method and the enzymatic synthesis so far are even less frequently used for the production of microbial inulin, as currently only a few sequences of bacterial inulosucrases have been fully described (Anwar et al 2008(Anwar et al , 2010Ortiz-Soto et al 2004;van Hijum et al 2002) and none of them have reached an application status neither for inulin synthesis nor for production of related oligosaccharides (FOS) (Vallejo-García et al 2019). However, inulin and FOS synthesized by microbial processes remain still considered (Vallejo-García et al 2019) to be a viable alternative to the fructans of vegetable origin that have been dominant so far (Olivares-Illana et al 2002;Mensink et al 2015;Vallejo-García et al 2019) and some promising results have also been achieved (Ozimek et al 2006;Peña-Cardeña et al 2015;Wada et al 2005). Only one strain L. citreum CW28 of Leuconostoc spp.…”
Section: Production Methods Strains and Optimum Conditionsmentioning
confidence: 99%
“…Only one strain L. citreum CW28 of Leuconostoc spp. has been studied very comprehensively and currently reported as capable of producing inulosucrase with the required characteristics for the enzymatic synthesis of inulin and/or FOS (Olivares-Illana et al 2002Oritz-Soto et al 2004;Peña-Cardeña et al 2015;Vallejo-García et al 2019). A bacterial strain from Leuconostoc spp.…”
Section: Production Methods Strains and Optimum Conditionsmentioning
confidence: 99%
See 1 more Smart Citation